2022
DOI: 10.3389/fphys.2022.941134
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of growth plate genes involved with the onset of femoral head separation in young broilers

Abstract: Femoral head separation (FHS) is characterized by the detachment of growth plate (GP) and articular cartilage, occurring in tibia and femur. However, the molecular mechanisms involved with this condition are not completely understood. Therefore, genes and biological processes (BP) involved with FHS were identified in 21-day-old broilers through RNA sequencing of the femoral GP. 13,487 genes were expressed in the chicken femoral head transcriptome of normal and FHS-affected broilers. From those, 34 were differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 94 publications
0
2
0
Order By: Relevance
“…The severity of disrupted cellular functions and overall bone homeostasis is becoming clearer as high-throughput omics studies are employed. Recent studies of the transcriptome and proteome revealed major alterations to bone development, cellular proliferation, and the immune response from normal bone [ 11 , 12 , 35 ]. Here, we found the differences between normal and FHN-affected bone to exist within the metabolome of these tissues as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The severity of disrupted cellular functions and overall bone homeostasis is becoming clearer as high-throughput omics studies are employed. Recent studies of the transcriptome and proteome revealed major alterations to bone development, cellular proliferation, and the immune response from normal bone [ 11 , 12 , 35 ]. Here, we found the differences between normal and FHN-affected bone to exist within the metabolome of these tissues as well.…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent study found differentially expressed cytokine and chemokine profiles in the local bone and blood of FHN-affected broilers compared to normal, healthy broilers [ 10 ]. Other researchers have utilized high-throughput transcriptomics and proteomics and identified key cartilage and bone growth as well as lipid metabolism and immune-related factors in FHS and FHN [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…They are predicted to affect the CUB2 domain, the second most common domain, followed by the serine protease domains, in which mutations causing 3MC syndrome have been frequently reported [37][38][39]. Although the mechanism of postnatal growth failure in 3MC syndrome is unclear, MASP1 has been indicated to play a role in extracellular biological processes, and its molecular function is related to calcium ion binding and ECM components [40].…”
Section: Discussionmentioning
confidence: 99%